Extramedullary haematopoiesis presented as intrathoracic tumour in a patient with alpha-thalassaemia - Bobylev, Dmitry (BioMed Central, 2013)
The authors report a case of extramedullary haematopoiesis (EMH) presenting as an intrathoracic tumour in a patient with alpha-thalassaemia. CT scan and MRI of the chest were obtained and followed by tumour excision. Compared to beta-thalassaemia, only two cases of EMH in patients with alpha-thalassaemia have been described in the literature. A possible reason for this disparity is discussed.